Brief Report: A Double-Blind, Placebo-Controlled, Crossover, Proof-of-Concept Study of Minocycline in Autism Spectrum Disorder - Erickson, Craig A.; Shaffer, Rebecca C.; Will, Meredith; Schmitt, Lauren M.; Horn, Paul; Hirst, Kathy; Pedapati, Ernest V.; Ober, Nicole; Tumuluru, Rameshwari V.; Handen, Benjamin L.; Beversdorf, David Q. (Journal of autism and developmental disorders, 2025)
Neuroinflammatory mechanisms have been implicated in the pathophysiology of autism spectrum disorder (ASD). Minocycline is a matrix metalloproteinase inhibitor 9 (MMP9) inhibitor tetracycline antibiotic with known anti-inflammatory properties. In preclinical animal models of ASD, minocycline has demonstrated potential positive effects on phenotypes that may have relevance to ASD. We conducted the first placebo-controlled study of minocycline in ASD. This double-blind, placebo-controlled crossover trial employed four week treatment periods with a two week washout period. Twenty-four 12–22 year olds (mean age 17.4 years; range 12.9–22.5 years) with ASD were enrolled. Overall minocycline was well tolerated. No minocycline-associated clinical changes were noted with treatment on any performance or clinician or caregiver completed measures were noted. We hypothesize that either minocycline does not have potential therapeutic effects in ASD or our project was underpowered to define potential subject subgroups who may potentially respond positively to this drug.